Containing anti-PLA2R IgG antibody induces podocyte injury in idiopathic membranous nephropathy - Ying Zhang; Ping Chen; Baobao Wang; Xueqing Tang; Yong Wei; Wei Cao; Lijun Tang; Zunsong Wang; Na Zhao (Renal Failure, 2023)
Background Idiopathic membranous nephropathy is widely recognized as an autoimmune kidney disease that is accompanied by the discovery of several autoantibodies, and the antibody subclass in the circulation of patients with iMN is mainly IgG. However, the direct pathogenic effect of the containing anti-PLA2R IgG antibody on podocytes is not clear.Method A protein G affinity chromatography column was used to purify serum IgG antibodies. Containing anti-PLA2R IgG antibodies from iMN patients and IgG from healthy controls were also obtained. Based on the established in vitro podocyte culture system, purified IgG antibodies from the two groups were used to stimulate podocytes, and the expression of essential podocyte proteins (podocin), the levels of inflammatory cytokines in the cell supernatant, cytoskeletal disorders, and podocyte apoptosis were analyzed.Results Compared with that in the normal IgG group, the expression of podocin and podocin mRNA was reduced (p = 0.016 and p = 0.005, respectively), the fluorescence intensity of podocin on the surface of podocytes was reduced, the cytoskeleton of podocytes was disordered and reorganized, and the ratio of podocyte apoptosis was increased in the iMN group (p = 0.008).Conclusion The containing anti-PLA2R IgG antibody might have a direct damaging effect on podocytes in idiopathic membranous nephropathy.